Enhanced Cu pillar design to reduce thermomechanical stress induced during flip chip assembly. (August 2018) - Lofrano, Melina; Cherman, Vladimir; Gonzalez, Mario; Beyne, Eric
Abstract: In this work a Cu pillar design that combines a stiff metal pedestal with a soft polymer as buffer layer has been integrated in a dedicated test vehicle to investigate the thermo mechanical stress induced during flip chip assembly. In-situ electrical measurements of dedicated stress sensors during a Bump Assisted BEOL Stability Indentation (BABSI) test were performed to assess the strength of the bump designs. Furthermore, the package induced stress was monitored in different regions of the test chips by measuring and comparing the ION current of the stress sensors before and after packaging. By combining in-situ electrical measurements and finite element modeling it was possible to quantify the stress level induced in the Si die after packaging. Additionally, the package out of plane deformation has been measured after flip chip to laminate and after molding. The results show that the use of a stiff pedestal is very efficient to mitigate packaging induced stress. It has also been shown that the out of plane deformation is independent of the Cu pillar design. Highlights: Analysis of different Cu pillar design that combines stiff and soft material to reduce stress induced during assembly The use of test vehicle that contains built in stress sensor In situ BABSE test on different Cu pillar design that results on assessment of Cu pillar strength Use of built in stress sensor combine with finite element modeling to understand the stress induced after packaging